A GUIDANCE SERVICES STUDENTS’ RECORD SYSTEM AT CEBU TECHNOLOGICAL UNIVERSITY ARGAO CAMPUS: RECORD SYSTEM DESIGN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Information Technology has brought about great benefits to society and organizations, particularly in terms of providing high-quality services that cater to people's needs. This study aimed to evaluate the existing student record system of the Guidance Services at Cebu Technological University-Argao Campus, as a basis for proposing a new record system design. The study utilized a descriptive survey and researcher-made questionnaires to collect data.